Dietary protein requirement and fishmeal replacement in tinfoil barb (Barbonymus schwanenfeldii Bleeker 1853) fingerlings - Mohd Puaad, Nuruljannah (2022)
Tinfoil barb, Barbonymus schwanenfeldii (Bleeker, 1854) is an indigenous cyprinid that has a big potential in the global ornamental fish industry and aquaculture. However, its nutrition and nutrient requirements have not been fully studied and understood while specific commercial feed for this species is unavailable. Protein is the most expensive nutrient in a diet and plays an important role in fish growth. In this study, three experiments were conducted to examine the protein requirements of the barb. An 8-week feeding trial was conducted in the Experiment 1 to determine the optimal dietary protein requirement for tinfoil barb (B. schwanenfeldii) fingerlings. Six isocaloric (17 kJ g-1 gross energy) diets were formulated to contain 25, 30, 35, 40, 45 and 50 % protein. Fingerlings (0.40 ± 0.03 g) were randomly stocked in 60 L glass aquaria at 25 fish per aquarium. Triplicate groups of fish were fed twice a day until satiation. The results showed that dietary protein level had significant effects on weight gain, specific growth rate, feed conversion ratio and protein efficiency ratio in tinfoil barb. Survival was not affected by the dietary protein level. Weight gain was significantly higher at 50% dietary protein (663.99 ± 24.51 %) compared to those of lower levels. Fish fed with 50% protein also showed significantly higher (P<0.05) specific growth rate (3.68 ± 0.30 % d-1) compared to fish fed 25-40 % protein. Feed efficiency improved with the increase in dietary protein level. FCR was less than 1.35 among fingerlings fed 45-50 % of dietary protein whereas fingerlings fed with 20-35 % protein had FCR of 1.7-2.0. In Experiment 2, six test diets were formulated to contain 40, 45 and 50 % protein with 17 and 18 kJ g-1 gross energy to determine if the optimal dietary protein of tinfoil barb could be reduced at a higher dietary energy. Similar rearing and feeding protocols as in Experiment 1 were adopted. The results showed that a higher dietary energy did not have a significant effect on final weight, weight gain, specific growth rate and feed efficiency of tinfoil barb. However, dietary protein had significant effects on fish growth (526.99 ± 30.35 %) and feed efficiency (1.32 ± 0.15) while its interaction with energy had significant effect on growth. Fish survival was not affected by the dietary protein and energy level, and their interaction. Fish fed 50% protein and 17 kJ g-1 gross energy showed significantly highest (P<0.05) specific growth rate (3.34 ± 0.12 % d-1) compared to fish fed with 40% protein and 17-18 kJ g-1 gross. Experiment 3 was conducted to evaluate the performance of fermented soybean meal as fish meal replacement in an effort to reduce feed cost. Five test diets were formulated to replace fish meal at 0, 25, 50, 75 and 100 %. The replacement level had a significant effect on final weight (4.43 ± 0.41 g), weight gain (455.34 ± 18.38 %), specific growth rate (2.79 ± 0.19 – 3.10 ± 0.29 % d-1), DFI (3.12 ± 0.19 – 3.18 ± 0.21 % BW d-1), FCR (1.25 ± 0.15) and PER (1.62 ± 0.18) but not CF, HSI and VSI. The results showed that fermented soybean meal could only replace up to 25% fishmeal in the diet of tinfoil barb. In conclusion, tinfoil barb had a high minimum dietary protein requirement of 45% at 17 kJ g-1 gross energy with fishmeal as a major protein source while fermented soybean meal could only replace up to 25% fishmeal in its diet.